Percentage of Available Nitrogen Content Based on Total Nitrogen Content in Peanut Plantations Before Harvest Using Organic Fertilizer Treatment - Nurmi, Nurmi; Azis, Muhammad Arief (International Journal of Technology and Education Research, 2025)
The study aims to determine the effect of organic fertilizers (chicken manure and burnt rice husks) on the percentage of NH4+ and NO3-, and to determine the correlation between total N with available N, as well as the correlation between the total percentage of available N with the yield of peanut plants (Arachis hypogaea L.). The study used a Randomized Block Design consisting of 3 treatment levels, namely: P0 = without organic fertilizer or control, P1 = 16 tons of organic chicken manure fertilizer ha-1, and P2 = 16 tons of organic burnt rice husk fertilizer ha-1. The results of this study indicate that only a small portion of the total N-in the soil is in the form of available N with the percentage of total available N only ranging from 0.028% - 0.063%. The total percentage of available N in chicken manure (0.053%) was higher than that of burnt rice husk fertilizer (0.048%) and the control (0.040%). There was a strong and very strong positive linear correlation between total N with available N, and there was a fairly strong positive linear correlation between the total percentage of available N with the number of pods and pod weight per plant.